Characteristics of Placebo Responders in Pediatric Clinical Trials of Attention-Deficit/Hyperactivity Disorder - Newcorn, Jeffrey H; Sutton, Virginia K; Zhang, Shuyu; Wilens, Timothy; Kratochvil, Christopher; Emslie, Graham J; D'Souza, Deborah N; Schuh, Leslie M; Allen, Albert J (Journal of the American Academy of Child and Adolescent Psychiatry, 2009)
Objective: Understanding placebo response is a prerequisite to improving clinical trial methodology. Data from placebo-controlled trials of atomoxetine in the treatment of children and adolescents with attention-deficit/hyperactivity disorder (ADHD) were analyzed to identify demographic and clinical characteristics that might predict placebo response in future clinical trials. Method: Data were pooled across 731 placebo-treated pediatric patients who participated in 10 acute, randomized, placebo-controlled trials. Responder status was based on empirically derived thresholds of change on the total score of the ADHD Rating Scale with minimal and robust response defined as 25% or greater and 40% or greater decrease, respectively. Study design characteristics, including randomization ratio, dose, and titration strategy, and patient demographic and clinical characteristics were examined as potential predictors of placebo response. Results: Inattentive subtype, lack of previous stimulant treatment, presence of comorbid tics and nonwhite ethnicity were associated with robust placebo response. A subset analysis of patients completing 6 weeks of treatment (to eliminate the effects of early dropout) identified inattentive subtype and lack of previous stimulant experience as significant predictors of robust placebo response. Conclusions: Placebo response is less likely in subjects with combined-subtype ADHD who are not stimulant-naive. Limiting ADHD clinical trials to this more restricted subject group is likely to maximize treatment differences. However, because this is not always possible or desirable, identifying other methods of mitigating placebo response is essential. (Contains 2 tables.)